Tonoplast Sugar Transporters (SbTSTs) putatively control sucrose accumulation in sweet sorghum stems. (2nd January 2016) - Bihmidine, Saadia; Julius, Benjamin T; Dweikat, Ismail; Braun, David M
ABSTRACT: Carbohydrates are differentially partitioned in sweet versus grain sorghums. While the latter preferentially accumulate starch in the grain, the former primarily store large amounts of sucrose in the stem. Previous work determined that neither sucrose metabolizing enzymes nor changes in Sucrose transporter ( SUT ) gene expression accounted for the carbohydrate partitioning differences. Recently, 2 additional classes of sucrose transport proteins, Tonoplast Sugar Transporters (TSTs) and SWEETs, were identified; thus, we examined whether their expression tracked sucrose accumulation in sweet sorghum stems. We determined 2 TSTs were differentially expressed in sweet vs. grain sorghum stems, likely underlying the massive difference in sucrose accumulation. A model illustrating potential roles for different classes of sugar transport proteins in sorghum sugar partitioning is discussed.